Super troopers 2 - Lowe, Rob; Chandrasekhar, Jay; Heffernan, Kevin; Lemme, Steve (Stephen Carlos); Soter, Paul, 1969-; Broken Lizard (Firm); Twentieth Century Fox Home Entertainment, Inc. (Beverly Hills, CA Twentieth Century Fox Home Entertainment, 2018)
When a border dispute arises between the U.S. and Canada, the Super Troopers are tasked with establishing a Highway Patrol station in the disputed area.
Originally released as a motion picture in 2018.
Special features: (Making) Super troopers 2; Kevin Heffernan: Method actor; extended & deleted scenes; theatrical trailers.
Jay Chandrasekhar, Kevin Heffernan, Steve Lemme, Paul Soter, Erik Stolhanske, Brian Cox, Lynda Carter, Rob Lowe.
Rating: R; for crude sexual content and language throughout, drug material and some graphic nudity.
Blu-ray, dts-HD Master Audio 5.1, region A, 1.85:1 widescreen; requires Blu-ray player.
DVD, widescreen; (1.85:1); Dolby digital 5.1 (English), Dolby digital 2.0 (French, Spanish); region 1.
Keywords: Traffic police -- Drama; Boundary disputes -- Drama; Comedy films; Drama; Feature films; Video recordings for people with visual disabilities; Video recordings for the hearing impaired